2005
DOI: 10.1177/030089160509100110
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Levels of Human Chromogranin a and Adrenomedullin in Patients with Pheochromocytoma

Abstract: Aims and background The aim of our study was to investigate the plasma chromogranin A (CgA) and adrenomedullin (AM) levels in patients with pheochromocytomas. Methods and study design We collected blood samples for measurement of plasma CgA and AM in 21 patients with pheochromocytomas, 43 healthy subjects and 26 patients with solid non-functioning adrenocortical adenomas. In 11 patients with pheochromocytomas plasma CgA and AM were measured again four weeks after tumor removal. CgA and AM were measured by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…This would suggest decreased catestatin is serving a pathophysiological role in the development of hypertension rather than being a consequence of elevated blood pressure. In contrast, plasma chromogranin A levels are increased in patients with pheochromocytoma or other chromaffin tumors [40], although catestatin levels have not yet been analyzed in these patients. Interestingly, a naturally occurring amino acid variant of catestatin, Gly364Ser, causes significant changes in human autonomic function and blood pressure.…”
Section: Catestatin and Catecholamine Releasementioning
confidence: 98%
“…This would suggest decreased catestatin is serving a pathophysiological role in the development of hypertension rather than being a consequence of elevated blood pressure. In contrast, plasma chromogranin A levels are increased in patients with pheochromocytoma or other chromaffin tumors [40], although catestatin levels have not yet been analyzed in these patients. Interestingly, a naturally occurring amino acid variant of catestatin, Gly364Ser, causes significant changes in human autonomic function and blood pressure.…”
Section: Catestatin and Catecholamine Releasementioning
confidence: 98%
“…Giovanella [12] suggested that a negative serum chromogranin A could rule out successive 123 I-MIBG imaging, but there are still too few studies to recommend the use of chromogranin A for pheochromocytoma screening. In one study the sensitivity of chromogranin A level was 90.2%, and its specificity 99.0%, with a significant relationship between serum levels of chromogranin A and tumor mass [13], whereas in another study chromogranin A had a sensitivity of 76.2%, a specificity of 97.7%, and an accuracy of 91% [14]. Larger studies are needed to better define the usefulness of chromogranin A in the diagnosis of pheochromocytoma.…”
mentioning
confidence: 99%
“…Our data does not support the use of CgA in the diagnosis of these tumors. Future collaborative studies to further investigate CgA in PCC/PGL diagnosis could involve CgA antisera from those centers where a positive role for CgA has been described (37,49,50). Adding plasma CART to the laboratory biochemical work-up for PCC/PGL diagnosis may be particularly valuable.…”
Section: Discussionmentioning
confidence: 99%